The efficacy of entrepreneurial networking and innovation in fostering the performance of small businesses in Uganda - Kasimu Sendawula; Moses Kisame Kisubi; Shamirah Najjinda; Hanifah Nantale; Samuel Kabbera (Journal of Innovation and Entrepreneurship, 2023)
The purpose of this study was to investigate the efficacy of entrepreneurial networking and innovation in fostering the performance of small businesses using evidence from Uganda. The study was cross-sectional and correlational. Data were collected through a self-administered questionnaire survey of 368 small businesses and analyzed through correlation, hierarchical regression, and mediation analysis using the Statistical Package for Social Sciences (SPSS). Study findings indicate that entrepreneurial networking and innovation are significant predictors of small business performance. Results also indicate that innovation partially mediates the relationship between entrepreneurial networking and the performance of small businesses. As such, this study contributes to the extant literature on the performance of small businesses as it provides initial empirical evidence on the efficacy of entrepreneurial networking and innovation in fostering the performance of small businesses. It further contributes to the recent literature on the mediation effect of innovation using evidence from Uganda.
Keywords: 650; Entrepreneurial networking; Innovation; Performance; Small business; Uganda